2005
DOI: 10.2170/jjphysiol.s655
|View full text |Cite
|
Sign up to set email alerts
|

Single-Channel Properties of Volume-Sensitive Cl− Channel in ClC-3–Deficient Cardiomyocytes

Abstract: It is controversial whether the ClC-3 protein, which is one of the voltage-dependent chloride channel ClC family members, is a candidate for the volume-sensitive outwardly rectifying (VSOR) Cl -channel per se or its regulator. Here, for the first time, we examined the single-channel properties of the VSOR Cl -channel in ventricular myocytes isolated from ClC-3-deficient mice. The single-channel current induced by cell swelling exhibited Cl -selectivity, mild outward rectification, and an intermediate unitary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…Other investigators have also found no difference in ICl swell between ClC-3 wild-type and null cells (17,48,50). This, however, contradicts studies showing that ClC-3 antibodies (9,11,55) and antisense oligonucleotides (22,51) inhibit ICl swell n a variety of cell types.…”
Section: Discussionmentioning
confidence: 86%
“…Other investigators have also found no difference in ICl swell between ClC-3 wild-type and null cells (17,48,50). This, however, contradicts studies showing that ClC-3 antibodies (9,11,55) and antisense oligonucleotides (22,51) inhibit ICl swell n a variety of cell types.…”
Section: Discussionmentioning
confidence: 86%
“…Unfortunately, other investigators have either been unable to express ClC-3 currents (8 -10) or have observed currents that were insensitive to changes in cell volume (10 -14). Importantly, ClC-3 null cells have consistently exhibited normal appearing whole-cell (15)(16)(17) and single channel (18) ICl swell currents. The regulation of ICl swell was, however, clearly altered in ClC-3 null cells (6).…”
mentioning
confidence: 99%
“…It was proposed that ClC-3 is a swelling-induced chloride conductance in NIH/3T3 cells stably transfected with ClC-3 cDNA (37). In addition, anti-ClC-3 antibodies and ClC-3 RNA interference strategies elicit impaired ICl swell activity in several cell types (38,47). However, the overexpression or absence of ClC-3 has no impact on the RVD in multiple cell types, including neurons (48), cardiac myocytes (38), and epithelial cells (49), indicating that ClC-3 is not ICl swell (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti-ClC-3 antibodies and ClC-3 RNA interference strategies elicit impaired ICl swell activity in several cell types (38,47). However, the overexpression or absence of ClC-3 has no impact on the RVD in multiple cell types, including neurons (48), cardiac myocytes (38), and epithelial cells (49), indicating that ClC-3 is not ICl swell (50,51). Most recently, Picollo and Pusch (52) reported that ClC-4 and -5, proteins in a subbranch of the ClC (chloride channel) gene superfamily that have 90% sequence homology to ClC-3, are in fact chloride/proton antiporters (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation